A Promising Application of Optical Hexagonal TaN in Photocatalytic Reactions. (15th November 2018) - Liu, Huimin; Song, Hui; Zhou, Wei; Meng, Xianguang; Ye, Jinhua
Abstract: Searching for highly active and efficient photocatalysts for photo‐induced/photo‐assisted reactions remains the most challenging task for solar energy utilization. In previous studies, the search for such materials has mainly focused on precious plasmonic metals (for example, Au, Ag, and Cu) and semiconductor oxides (for example, TiO2, ZnO, and WO3 ). Herein, we report the application of hexagonal tantalum mononitride (TaN) as an optical support in photocatalytic reactions, which could harness visible light to assist CO2 conversion and decompose organic pollutants. Theoretical studies indicated that the improved electron‐hole separation in polar TaN under visible‐light illumination was critical for its use in photocatalysis. This study could guide the use of TaN in various photocatalytic reactions and wider optical applications. Abstract : TaN wurde aufgrund seiner optischen Eigenschaften für eine photokatalytische Reaktion verwendet. Dabei wurde gezeigt, dass die verbesserte Elektron‐Loch‐Trennung und der erhöhte Elektronentransfer in asymmetrischem TaN die erhöhte Aktivität unter Bestrahlung mit sichtbarem Licht erklärt.